Can Chat GPT Replace the Role of the Teacher in the Classroom: A Fundamental Analysis - Abu Muna Almaududi Ausat; Berdinata Massang; Mukhtar Efendi; Nofirman Nofirman; Yasir Riady (Departement of Mathematics Education, 2023)
The background of this study relates to an exploration of the role of technology in the classroom learning process, especially in terms of shifting the role of the teacher as the main instructor. The rapid and ever-changing development of technology has had a huge impact on education systems around the world, such as ChatGPT. This study will conduct an in-depth analysis of ChatGPT's ability to replace the role of teachers in the classroom learning process. This research is qualitative in nature. The methodology used to collect data includes attentive listening and careful documentation of relevant information, which is then subjected to analytical procedures such as data reduction, data display, and conclusion drawing. The study arrived at the conclusion that in the context of using ChatGPT in learning, it should be noted that technology can only be a tool and cannot replace the role of the teacher entirely. Therefore, it is necessary to integrate technology in learning in an appropriate and effective way and develop competence for teachers in managing learning with technology.